Acute and subchronic antihyperglycemic activities of bowdichia virgilioides roots in non diabetic and diabetic rats - Silva, Ana (2015)
Aim: The present study was undertaken to evaluate the acute and subchronic antihyperglycemic effects of methanolic extract of B. virgilioides root bark of B. virgilioides in streptozotocin-induced diabetic rats.Materials and Methods: The extract (100, 250 or 500 mg/kg) was orally administered to male Wistar diabetic (streptozotocin, 42 mg/kg i.v.) and non-diabetic rats into two main protocols: i) subchronic experiments, where animals were treated for 21 days with B. virgilioides extract and the following parameters were evaluated: body weight, fluid and food intake (determined daily), urinary glucose and urea (every 3 days) and glycemia (every 5 days). At the end of the experimental period, skeletal muscles (extensor digitorum longus and soleus), retroperitoneal and epididymal white adipose tissues were collected and weighed; liver samples were used for the determination of the lipid and glycogen contents; ii) acute experiments, which evaluated the alterations on fasting and post-prandial glycemia and on glucose tolerance using the oral glucose tolerance test (OGTT).Results: In subchronic experiments, the treatment with B. virgilioides extract did not change any parameter evaluated in diabetic and non-diabetic animals. On fasting and post-prandial glycemia, the extract treatment did not promote changes in the glycemia values in diabetic or non-diabetic animals. In OGTT, the treatment with 500 mg/kg B. virgilioides extract reduced the hyperglycemia peak after a glucose overload, when compared with non-treated diabetic animals, resulting in a lower area under curve (AUC). Conclusion: The results of our work indicate that B. virgilioides root extract promotes an acute antihyperglycemic effect in STZ-diabetic rats; this effect probably occurs through an inhibition of the intestinal glucose absorption. The continuity of the research is necessary to elucidate these possibilities.